The Topography of the Athenian Plain under Ottoman Rule (1456-1821) - Pallis, Georgios (The Historical Review/La Revue Historique, 2008)
Τhe settlements that developed in the Athenian plain under Ottoman rule are the subject of the following paper. According to the written sources and the surviving monuments, 25 villages and 14 monasteries were spread throughout the area. After a remarkable period of prosperity in the sixteenth century, most of them fell into a continuous state of decline, until the end of the Ottoman era. The history and the organisation of these settlements, the road network that connected them and domestic and church architecture are put under investigation, in order to reconstruct as much as possible the map and the picture of the area during this long period.